Relational Premises in the Cooperation Between Farms with Conservative Breeds and Industry Organisations - Marta Domagalska-Grędys (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The main aim of the study was to indicate relational premises in the cooperation between industry organisations and farms with conservative breeds (cattle, pigs, and sheep). It has been assumed that the processes of integration of domestic animal breeders depend on the state of the relationships established (in terms of quality, sustainability, dependence and uniqueness) with industry organisations. The research was carried out on the basis of an interview questionnaire (in 2017) with farmers from south-eastern Poland, representatives of organisations, and a review of secondary sources describing the activities of industry organisations since the beginning of their existence. The specificity of the entities under analysis stems from their role and responsibilities. Breeders contribute to the growth of biodiversity, while industry organisations are an important partner in their relationships as they support farms (they mediate in the contracting process, organise trainings, represent the interests of producers in Poland and abroad). Preliminary results of the research indicate that the best conditions for cooperation are in the networks of breeders of conservative breeds of pigs as well as in interorganisational relationships with the ‘POLSUS’ industry organisation.